The age and colors of massive white dwarf stars - Althaus, Leandro Gabriel (2007)
Aims. We present evolutionary calculations and colors for massive white dwarfs with oxygen-neon cores for masses between 1.06 and 1.28 M ⊙. The evolutionary stages computed cover the luminosity range from log(L/L⊙) ≈ 0.5 down to -5.2. Methods. Our cooling sequences are based on evolutionary calculations that take into account the chemical composition expected from massive white dwarf progenitors that burned carbon in partially degenerate conditions. The use of detailed non-gray model atmospheres provides us with accurate outer boundary conditions for our evolving models at low effective temperatures. Results. We examine the cooling age, colors and magnitudes of our sequences. We find that massive white dwarfs are characterized by very short ages to such an extent that they reach the turn-off in their colors and become blue at ages well below 10 Gyr. Extensive tabulations for massive white dwarfs, accessible from our web site, are also presented.